Co-construcción de soluciones barriales participativas, caso de estudio: “Barrio Isidro Ayora” parroquia y cantón Catamayo, provincia de Loja, periodo abril - septiembre 2022 - Alondra Mariuxi, Calva Jiménez (2023)
The research is aimed at contributing to the Isidro Ayora neighborhood of the Catamayo canton in the province of Loja in the formulation of participatory solutions in terms of citizen demands and local reality; promoting neighborhood organization, assisting the neighborhood in the development of collective diagnoses of the problems and supporting the design of solutions to the problems identified by the community. In order to achieve the objectives, an action research methodology was used, as well as techniques and methodological tools for gathering information such as participatory workshops, training, observation sheets, surveys and interviews with key actors in the sector. This allowed us to get closer to the neighborhood leaders and residents of the neighborhood, to make them aware of the project of Co-construction of participatory neighborhood solutions and to learn about the problems that the neighborhood is going through. Through methodological tools such as the observation guide and survey, qualitative variables such as (security, signage, infrastructure and environment) were evaluated, obtaining as a result (lack of a physical place for the neighborhood organization; insecurity, caused by the absence of street lighting; and finally, the lack of asphalting and maintenance of streets, which generates difficulty in transit and excessive dust), these problems were validated with the residents. After this, a plan of action was drawn up establishing possible solutions to the problems identified through the implementation of a timetable that was handed over to the president of the neighborhood for future implementation by the competent authorities.